Image-Guided Radiotherapy for Cardiac Sparing in Patients with Left-Sided Breast Cancer - Lemanski, Claire; Thariat, Juliette; Ampil, Federico L.; Bose, Satya; Vock, Jacqueline; Davis, Rick; Chi, Alexander; Dutta, Suresh; Woods, William; Desai, Anand; Godinez, Juan; Karlsson, Ulf; et al. (Frontiers in Oncology, 2014)
Patients with left-sided breast cancer are at risk of cardiac toxicity because of cardiac irradiation during radiotherapy with the conventional 3-dimensional conformal radiotherapy technique. In addition, many patients may receive chemotherapy prior to radiation, which may damage the myocardium and may increase the potential for late cardiac complications. New radiotherapy techniques such as intensity-modulated radiotherapy (IMRT) may decrease the risk of cardiac toxicity because of the steep dose gradient limiting the volume of the heart irradiated to a high dose. Image-guided radiotherapy (IGRT) is a new technique of IMRT delivery with daily imaging, which may further reduce excessive cardiac irradiation. Preliminary results of IGRT for cardiac sparing in patients with left-sided breast cancer are promising and need to be investigated in future prospective clinical studies.